Neurovascular uncoupling of cerebral blood flow and glucose metabolism in APOE4, TREM2, and APOE4.TREM2 mice: Development of new models and analysis methods/novel assays and technologies. (7th December 2020) - Territo, Paul R.; Lin, Peter B.; Persohn, Scott C.; Bedwell, Amanda A.; Eldridge, Kierra; Speedy, Rachael; Kotredes, Kevin P.; Pandey, Ravi S.; Oblak, Adrian L.; Sasner, Michael; Carter, Gregory W.; Lamb, Bruce T.; et al.
Abstract: Background: Alzheimer's disease (AD) is the most common cause of dementia in the United States, with approximately 95% of patients exhibiting sporadic Late‐Onset AD (LOAD), which lacks an inheritance pattern. Therefore, identifying phenotypic patterns are critical for understanding disease progression. Apolipoprotein E4 (APOE4), the strongest genetic risk factor of LOAD, increases AD risk by 3‐12 fold depending on copy number. Recent GWAS analysis elucidated the LOAD‐associated loci on the triggering receptor expressed on myeloid cell 2 (TREM2). APOE is a known ligand to the TREM2 receptor, and the R47H variant could increase the AD risk by 2‐3 fold. Preclinical studies of these risk alleles and their phenotypes are underway by MODEL‐AD. Methods: Using PET/MRI and a novel analytical scheme, we established the perfusion‐metabolism profiles across 27 brain regions in both sexes by using 64 Cu‐PTSM and 18 F‐FDG in the APOE4 ( APOE E4/E4 ), TREM2 ( TREM2 R47H ), and double ( APOE E4/E4 . TREM2 R47H ) knockin (KI) mice, and compared these to blood chemistry and nanoString transcriptomic analysis. Results: Longitudinal analysis comparing 12mo to 4mo time point revealed that male APOE4 mice and both sexes of TREM2 had hypo‐ perfusion and metabolism, while female APOE4 mice showed an uncoupled hyper‐perfusion and hypo‐metabolism phenotype, and was correlated to human AD pathology. In double KI mice, perfusion and metabolism showed a mixed phenotype which was region dependent. Cross‐sectional analysis of KI compared to C57BL/6J mice at 12mo showed an overall reduced glucose metabolism. Intriguingly, male APOE4, TREM2, and double mice showed hypo‐perfusion and metabolism, while female double mice showed metabolic uncoupling compared to C57BL/6J. Analysis of blood biochemistry in non‐fasted mice revealed no significant difference between genotypes in blood glucose with age. However, APOE4 decreased the blood cholesterol level (LDL, and HDL). RNAseq and immunohistology was peformed, and key genes involved in the regulation of cerebral perfusion, glucose transportation, and metabolism were altered. Conclusions: These data suggest that the new perfusion‐metabolism strategy may be able to identify AD‐related patterns. Moreover, they replicate clinical manifestations of subjects with the same variants, suggesting additional mechanistic studies are needed to elucidate the mechanisms and etiology of this uncoupling phenomenon.